Professional nurse advocates and restorative clinical supervision: national survey of programme implementation and impact - Liz Lees-Deutsch; Shea Palmer; Amanda Rodrigues Amorim Adegboye; Natasha Bayes; Aiden Chauntry; Emma Wadey; Rosie Kneafsey (BMC Nursing)
Abstract Background In 2021, a new national Programme of clinical nurse leadership, called the Professional Nurse Advocate Programme, was launched across the National Health Service of England. The primary aim was to support nurse wellbeing and resilience in the aftermath of Covid-19 pandemic. Trained nurse advocates offered restorative clinical supervision sessions to nurses, career conversations through the Advocating and Educating for Quality Improvement model, aiming to sustain their motivation at work through improved wellbeing. This paper evaluates the national Programme delivered across England. Methods Cross-sectional questionnaire, underpinned by Laschinger’s model of empowerment, distributed across England in 2022. This explored the effectiveness and impact of Restorative Clinical Supervision on nurse empowerment, and personal effectiveness. The questionnaire sections included demographics and 14 questions to understand restorative clinical supervision in practice; respondents’ abilities to fulfil PNA roles and responsibilities; and four open text questions. Demographic data were analysed using descriptive statistics. Open text responses were coded to generate themes. Results There were 302 questionnaire responses from nurses receiving restorative clinical supervision n = 73, Professional Nurse Advocates n = 214 and leads n = 15, most were female and identified as ‘white’ ethnicity. Restorative clinical supervision was rated very positively, enhancing structural and psychological empowerment. Three primary themes were identified from open-ended questions; (i) Conditions necessary for restorative supervision; (ii) Nurse engagement and organisational commitment to restorative supervision and (iii) Reinvigoration from supervision. Conclusion We established that the professional clinical leadership role of the nurse advocates offers individual support through reflective practice and strategies to address resilience. Spaces of safety and adequate time are reported as fundamental to delivering the advocate role, plus time for nurses to be released from clinical duties to participate in restorative supervision. Since the roll out of the Programme 10,933 training places have been funded, representing significant investment. 78,187 restorative clinical supervision sessions; 49,595 career conversations and 2,541 Quality Improvement projects were underway in October 2024. This is the first national evaluation of the Programme and findings indicate its potential to address underlying global nursing concerns linked to workforce attrition, wellbeing in the workplace, retention, and recognition of nurse impact. Public or Patient Contribution Not applicable. Clinical trial number Not applicable.